Migraine therapeutics in adolescents: a systematic analysis and historic perspectives of triptan trials in adolescents - Sun, Haihao; Bastings, Eric; Temeck, Jean; Smith, P Brian; Men, Angela; Tandon, Veneeta; Murphy, Dianne; Rodriguez, William (JAMA pediatrics, 2013)
OBJECTIVES To conduct a systematic review and analysis of trial data submitted to the US Food and Drug Administration (FDA) to identify possible causes for the failure of pediatric trials of triptans for treatment of migraines. DATA SOURCE The FDA website for drug information and published literature. STUDY SELECTION All pediatric efficacy and pharmacokinetics trial data of drugs used for abortive treatment of migraine submitted to the FDA from January 1, 1999, through December 31, 2011. MAIN OUTCOME MEASURES Patient demographic baseline characteristics, inclusion and exclusion criteria, trial designs, efficacy end points, and pharmacokinetic profiles were analyzed and compared across drug products. RESULTS We analyzed data for sumatriptan succinate nasal spray and zolmitriptan, eletriptan hydrobromide, almotriptan malate, and rizatriptan benzoate tablets. Seven efficacy trials had a randomized, double-blinded, placebo-controlled, parallel-group trial design. In 4 trials, patients were required to have a history of migraine attacks lasting at least 4 hours. High response rates for placebo were observed in all trials, with pain relief at 2 hours ranging from 53% to 57.5%. Nonrandomization of patients with an early placebo response design was used in the rizatriptan trial in 2011. Compared with the rizatriptan trial conducted in 1999, the 2011 rizatriptan trial reduced the placebo response rate by 6% for headache freedom at the 2-hour posttreatment end point owing to study design. The pharmacokinetic profiles between adolescents and adults were statistically similar. CONCLUSIONS High placebo response rates are consistent across all trials and may represent the principal challenge in pediatric trials of drugs for abortive treatment of migraine. Enrichment with selection of subjects with long-lasting migraine attacks is not sufficient to overcome high placebo response rates. Another enrichment strategy, the nonrandomization of patients with an early placebo response, successfully reduces the high placebo response rate for rizatriptan and is a trial design that should be considered for future pediatric trials of abortive migraine therapeutics.